THE DEVELOPMENT STORY IN THE REFLECTION OF HISTORY - Abdullah, Taupik (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2011)
Statement of Bismark, the Prusia chancellor was right, â€œClever people,â€ he said, â€œlearn from his own experiece. I learn from otherâ€™s experienceâ€. Otherâ€™s experience? It means he learn from history, then he could unite Germany. Today we also face a problem in education. In this beloved homeland, history lesson has been ignored, eventhough this nation was formed from the understanding and awareness of history, and this country leaders have spoken about nationâ€™s character development. Someone with better understanding could explain the reason of this odd policy. Understanding and awareness of history are needed to overcome various problems faced by this nation. In this very obvious imbalance, do we need to wonder about the decrease of Human Development Index? In their release, UNDP explained that Indonesia curent (2011) posistion is 124 (index value of 0.617) from 187 countries . Thus, when a personal and social conflicts that have been provoked by the unfair economy imbalance were related to the relgion and ethnic, a bloody conflict could not be avoided and even worse it was spreaded to various other problems. Many people had been the victims, not to mention the hatred in their heart, before peace could be realized.